Exploring the Perspectives of Healthcare Professionals (HCPs) on “Pulmonary Rehabilitation” for Persons with Chronic Respiratory Diseases (CRD) – A Cross-Sectional Study - V.S., Saril (Digital Repository of Theses, 2026)
The healthcare business industry is quite unique compared to other business sectors and its primary goal is not just profit, as healthcare is an essential human right and needs to focus on enhancing Quality of Life of its beneficiaries. Rehabilitation Medicine is an emerging and highly significant business vertical in the healthcare industry, however, the need for rehabilitation is largely unmet especially in the developing countries. Chronic Respiratory Diseases (CRDs) represent a major global health burden. Pulmonary Rehabilitation (PR) is an evidence-based non-pharmacological intervention for managing CRDs. Globally, PR service availability is critically low, and its awareness is extremely limited in a developing country like India though CRD is the 2nd leading cause of death and disability, making it a nationwide public health threat requiring immediate attention. Despite the strong scientific recommendations, referral to and uptake of PR programs remain disproportionately low, and implementation of PR service remains inconsistent. Health care professionals (HCPs) play a very important role in aiding PR as a sustainable business model. This study explores the perspectives of HCPs on PR services, focusing on their beliefs, referral practices, perceived barriers and potential strategies to facilitate PR business implementation as a frontier healthcare vertical. In response to this gap, we established a unique pulmonary rehabilitation facility, aligned with globally accepted, evidence-based standards. A Kaizen-based continuous improvement method was used to gradually increase program quality, and longitudinal clinical audits were used to track program efficacy. The viability of PR as a long-term service delivery strategy was established by consistently positive clinical performance, rising service uptake, and high patient happiness as determined by Net Promoter Scores. The importance of healthcare professionals in facilitating scalability was brought to light by this practical implementation experience, which inspired the current study to investigate the opinions of care providers regarding the adoption of PR services in India. A quantitative descriptive cross-sectional survey was conducted among HCPs (n=232) involved in CRD management. As per our knowledge, this is the first-of-its-kind comprehensive Indian study, encompassing 23 different disciplines comprising both clinical fraternity and administrators. A structured questionnaire based on 5 pointer Likert scale assessed knowledge, attitudes, beliefs, referral practices and implementation perspectives. The study showed that healthcare professionals had a high level of knowledge and professional confidence on pulmonary rehabilitation. Overall, 69% of respondents said they were prepared to refer eligible patients, and 73.2% of respondents assessed their understanding of PR eligibility requirements at ≥8 on a 10-point scale. The availability and accessibility of PR services in India were assessed low when compared to worldwide standards (mean score 1.75/10), despite a significant consensus regarding the necessity for high-quality PR centers in India (mean score 9.08/10). Clinical severity and functional impairment were the main factors influencing referral decisions, whereas systemic and patient-level obstacles, such as restricted access to PR centers, transportation difficulties, and patient refusal, were the main causes of non-referral rather than a lack of faith in PR efficacy. Most HCPs acknowledged the benefits of PR services but barriers such as awareness, unclear referral services, inadequate resources, and poor access limits integration into routine CRD care in the healthcare industry. Preliminary findings indicate variability in awareness among HCPs with respiratory specialists demonstrating greater familiarity compared to other potential referral and service providers. Addressing gaps in awareness, role clarity, and resource allocation, alongside developing accessible PR business models in India, is crucial to strengthen referral practices, optimize patient participation and outcomes. There is tremendous potential for establishing high quality PR delivery centres across Indian healthcare industry, which could contribute in alleviating the disease burden nationally and globally. It is an emerging business model, easily adaptable even in the low resource settings of developing countries. India could set an example of a sustainable healthcare model by establishing robust policies, availability and accessibility of PR services for those suffering from crippling chronic conditions by improving their overall health status to lead a dignified life and this study’s implications pave way for the same. Alleviating human suffering is the best that scientific business studies could contribute to building a nation that prioritizes its people’s health. Keywords: Pulmonary Rehabilitation, Chronic Respiratory Disease, Healthcare Professionals, referral practices.